Association between COVID-19 burden and delays to diagnosis and treatment of cancer patients in England. (March 2022) - Fox, Louis; Monroy-Iglesias, Maria J.; Aggarwal, Ajay; Haire, Kate; Purushotham, Arnie; Spicer, James; Papa, Sophie; Rigg, Anne; Dolly, Saoirse; Sullivan, Richard; Van Hemelrijck, Mieke
Highlights: Increased local COVID-19 burden was associated with lower compliance with 62-day 'Cancer Waiting Time' (CWT) targets amongst urgent pathway referrals. No associations were found between internal specialist referrals and compliance with 62-day CWT targets, during both waves of COVID-19. 62-day CWT was not affected by a high COVID-19 burden for various tumour types. However, a decrease was seen in the number of patients treated during the first wave of COVID-19. These results are consistent with anecdotal experiences of many clinicians working in England's National Health Service. Abstract: Background: The COVID-19 pandemic has been highly disruptive for cancer care. Here, we examined the effect COVID-19 had on performance of the 62-day Cancer Waiting Time (CWT) target set by the National Health Service (NHS) in England. Methods: Data were retrospectively obtained on COVID-19 hospitalisations and CWT for NHS hospitals in England (n = 121). We produced a 'COVID-19 burden' to describe the proportion of each provider's beds occupied with COVID-19 patients. COVID-19 burden was examined against CWT performance for 1st April – 30th May 2020 (Wave 1), and 1st October – 30th November 2020 (Wave 2). Two-tailed Spearman correlations were used to identify relationships between COVID-19 burden and CWT performance amongst different referral (i.e., 2-week-wait (2 W W) and internal specialist) and tumour types. Significantly correlated variables were further examined using linear regression models. Results: COVID-19 burden was negatively associated with the percentage of 2 W W pathway referrals that met the CWT target in Wave 1 (r= -0.30, p = 0.001) and Wave 2 (r= -0.21, p = 0.02). These associations were supported by the results from our linear regression models (B for wave 1: -0.71; 95 %CI: −1.03 to −0.40; B for wave 2: -0.38; 95 %CI: −0.68 to −0.07). No associations were found between COVID-19 burden and internal specialist referrals or tumour type. Conclusion: Increased COVID-19 burden was associated with lower compliance with CWT targets amongst urgent referrals from primary care in England. This will likely be an ongoing issue due to the backlog of patients awaiting investigations and treatment. Policy summary: As the number of cancer referrals improve, we highlight the need for changes to primary and secondary care to manage the backlog within cancer diagnostic services to alleviate the impact of COVID-19.